Effectiveness of TENS and home exercises as an adjunct to drug therapy in the management of myogenous masticatory pain: a comparative study - Kandagal Veerabhadrappa Suresh; Anbananthan Thurka Devi; Ying Chee Xin; Ramamurthy Priyadarshini Hesarghatta; Yadav Seema; Bin Zamzuri Ahmad Termizi (EDP Sciences, 2021)
Introduction: Pain relief is the primary goal of treatment in patients with myogenous temporomandibular disorder. This study evaluated the effectiveness of TENS and Home exercises as an adjunct to drugs in relieving myogenous masticatory pain. Materials and methods: This prospective clinical study was conducted on 60 patients with myogenous masticatory pain. Patients were randomly allocated into three groups of 20 patients each. Patients in Group A received TENS and drugs, while patients in Group B received home exercises and drugs and Group C received drugs only. The drugs prescribed were Diclofenac 50 mg and Orphenadrine 100 mg, to be taken twice daily for 5 days. All patients were followed up for three weeks. The severity of pain was recorded using the Visual Analog Scale. Inter and intragroup differences in the pain scores were analyzed using one-way ANOVA along with post hoc Tukey's test, and Paired t-test, respectively. p < 0.05 was considered as statistically significant. Results: There was a significant reduction in the mean pain scores in all the three groups at 1st, 2nd, and 3rd post-treatment weeks as compared to the baseline scores with p < 0.001. However, when the pain scores were compared across groups, maximum pain reduction was observed in group A (0.2 ± 0.04), followed by group B (0.5 ± 0.06), and the least reduction was noticed in group C (2.1 ± 0.8). This result was significant with p < 0.001. Conclusion: Both TENS and Home exercises program were effective as adjuncts to drugs, in controlling myogenous masticatory pain, as compared to drugs alone.